Adcitmer®, a new CD56‐targeting monomethyl auristatin E‐conjugated antibody, is a potential therapeutic approach in Merkel cell carcinoma. (2nd November 2021) - Esnault, C.; Leblond, V.; Martin, C.; Desgranges, A.; Baltus, C.B.; Aubrey, N.; Lakhrif, Z.; Lajoie, L.; Lantier, L.; Clémenceau, B.; Sarma, B.; Schrama, J.; et al.
Summary: Background: Merkel cell carcinoma (MCC) is an aggressive skin cancer, whose tumour cells often express CD56. While immune checkpoint inhibitors constitute a major advance for treating patients with MCC with advanced disease, new therapeutic options are still urgently required. Objectives: To produce and evaluate the therapeutic performance of a new antibody–drug conjugate (Adcitmer ® ) targeting CD56 in preclinical models of MCC. Methods: CD56 expression was evaluated in a MCC cohort (immunohistochemistry on a tissue microarray of 90 tumour samples) and MCC cell lines. Interaction of an unconjugated CD56‐targeting antibody with CD56 + MCC cell lines was investigated by immunohistochemistry and imaging flow cytometry. Adcitmer ® product was generated by the bioconjugation of CD56‐targeting antibody to a cytotoxic drug (monomethyl auristatin E) using the McSAF Inside ® bioconjugation process. The chemical properties and homogeneity of Adcitmer ® were characterized by hydrophobic interaction chromatography. Adcitmer ® cytotoxicity was evaluated in vitro and in an MCC xenograft mice model. Results: Similar to previous reports, CD56 was expressed by 66% of MCC tumours in our cohort, confirming its relevance as a therapeutic target. Specific binding and internalization of the unconjugated CD56‐targeting antibody was validated in MCC cell lines. The high homogeneity of the newly generated Adcitmer ® was confirmed by hydrophobic interaction chromatography. The CD56‐mediated cytotoxicity of Adcitmer ® was demonstrated in vitro in MCC cell lines. Moreover, Adcitmer ® significantly reduced tumour growth in a MCC mouse model. Conclusions: Our study suggests that Adcitmer ® should be further assessed as a therapeutic option in patients with MCC, as an alternative therapy or combined with immune checkpoint inhibitors. Abstract : What is already known about this topic? Merkel cell carcinoma (MCC) is an aggressive skin cancer. While immune checkpoint inhibitors constitute a major advance in treating patients with MCC with advanced disease, new therapeutic options are still urgently required. CD56, which is expressed by most MCC tumours, might constitute a therapeutic target for the development of antibody–drug conjugate therapies. What does this study add? We generated a CD56‐targeting monomethyl auristatin E (MMAE) bioconjugate antibody (Adcitmer ® ) and demonstrated its optimal biochemical properties, specific binding and cytotoxicity in vitro in MCC cell lines, and its capacity to reduce tumour growth in vivo in a MCC mouse model. What is the translational message? Adcitmer ®, a new CD56‐targeting MMAE bioconjugate antibody, may represent a potential therapeutic option to be investigated as an alternative approach or in combination with immune checkpoint inhibitors in patients with inoperable MCC. Linked Comment:  L. Leiendecker et al. Br J Dermatol 2022; 186:209–210 . Plain language summary available online